2021
DOI: 10.3390/biom11111718
|View full text |Cite
|
Sign up to set email alerts
|

A Novel miRNA Screen Identifies miRNA-4454 as a Candidate Biomarker for Ventricular Fibrosis in Patients with Hypertrophic Cardiomyopathy

Abstract: (1) Background: Left ventricular hypertrophy, myocardial disarray and interstitial fibrosis are the hallmarks of hypertrophic cardiomyopathy (HCM). Access to the myocardium for diagnostic purposes is limited. Circulating biomolecules reflecting the myocardial disease processes could improve the early detection of HCM. Circulating miRNAs have been found to reflect disease processes in several cardiovascular diseases. (2) Methods: We quantified circulating miRNA molecules in the plasma of 24 HCM and 11 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…They found that only miR-133a could be a biomarker independently associated with the decrease in thr carboxy-terminal propeptide of type-I collagen (PICP, (β-value = 6.43, 95% confidence interval (CI): 12.71 to −0.15), which would be correlated with collagen synthesis and myocardial fibrosis [ 111 , 112 ]. Recently, Thottakara et al reported that the plasma level of miR-4454 was significantly correlated with the extent of cardiac fibrosis detected by late gadolinium enhancement (LGE) on magnetic resonance imaging (MRI) (r = 0.56) and septal wall-thickness (r = 0.38) in patients with hypertrophic cardiomyopathy (HCM) [ 71 ].…”
Section: Potential Clinical Application Of Mirnas In Cardiac Fibrosismentioning
confidence: 99%
“…They found that only miR-133a could be a biomarker independently associated with the decrease in thr carboxy-terminal propeptide of type-I collagen (PICP, (β-value = 6.43, 95% confidence interval (CI): 12.71 to −0.15), which would be correlated with collagen synthesis and myocardial fibrosis [ 111 , 112 ]. Recently, Thottakara et al reported that the plasma level of miR-4454 was significantly correlated with the extent of cardiac fibrosis detected by late gadolinium enhancement (LGE) on magnetic resonance imaging (MRI) (r = 0.56) and septal wall-thickness (r = 0.38) in patients with hypertrophic cardiomyopathy (HCM) [ 71 ].…”
Section: Potential Clinical Application Of Mirnas In Cardiac Fibrosismentioning
confidence: 99%
“…The literature regarding the association of circulating miR-499 with HCM is still limited and contradictory. The level of miR-499a-5p was higher in the plasma of HCM patients than of healthy controls [ 35 ]. In another study no significant differences were observed for miR-499-5p when analyzing 41 HCM patients and 41 age- and sex-matched healthy controls [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-499 was shown to regulate the cardiac β-MyHC/α-MyHC ratio, and β-MyHC expression was increased in human hearts of patients with ischemic cardiomyopathy and other heart diseases [ 23 , 24 , 25 , 26 ]. Circulating miR-499a-5p was proven as one of the dysregulated miRNAs in HCM, which expressed higher in HCM patients than in healthy controls, and carriers of P/LP variants in the MYH7 gene expressed higher levels than in controls [ 27 , 28 ]. In our study, we found that myocardial miR-499a-5p was also up-regulated, and higher expression of myocardial miR-499a-5p correlated with lower LVEF.…”
Section: Discussionmentioning
confidence: 99%